Fabrication of gentamicin sulfate-loaded 3d-printed polyvinyl alcohol/sodium alginate/gelatin-methacryloyl hybrid scaffolds for skin tissue replacement - ULAĞ, SONGÜL; ŞAHİN, ALİ; AKSU, MEHMET BURAK; GÜNDÜZ, OĞUZHAN (My University, 2023)
3D-printed scaffolds can better mimic the function of human skin, both biologically and mechanically. Within the scope of this study, the effect of the addition of different amounts (10, 15, 20 mg) of gentamicin sulfate (GS) to a 10 mL solution of natural and synthetic polymers is investigated. Sodium alginate (SA), gelatin-methacryloyl (GelMA), and polyvinyl alcohol (PVA) are chosen as bioactive materials. The surface morphology and pore structures are visualized by scanning electron microscopy (SEM). According to the results, it is observed that the pore sizes of all scaffolds are smaller than 270 µm, the lowest value (130 µm) is obtained in the scaffold loaded with 15 mg GS, and it also has the highest tensile strength value (12.5 ± 7.6 MPa). Similarly, it is observed that the tensile strength (9.7 ± 4.5 MPa) is high in scaffold loaded with 20 mg GS. The biocompatibility test is performed with fibroblast cells, and the results show that the scaffolds are biocompatible with cells. The antibacterial test is carried out against the S.aureous and E. coli and the results indicate that all GS-loaded scaffolds demonstrate antibacterial activity.
Keywords: Kimya Mühendisliği ve Teknolojisi; Kimya; Biyokimya; Biyoinorganik Kimya; Fizikokimya; Polimer Karakterizasyonu; Temel Bilimler; Mühendislik ve Teknoloji; Chemical Engineering and Technology; Chemistry; Biochemistry; Bioinorganic Chemistry; Physical Chemistry; Characterization of Polymers; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; Malzeme Bilimi; MÜHENDİSLİK, KİMYASAL; POLİMER BİLİMİ; KİMYA, ORGANİK; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; MATERIALS SCIENCE; CHEMISTRY; ENGINEERING, CHEMICAL; POLYMER SCIENCE; CHEMISTRY, ORGANIC; MATERIALS SCIENCE, MULTIDISCIPLINARY; Genel Kimya Mühendisliği; Fizik Bilimleri; Polimerler ve Plastikler; Organik Kimya; Malzeme Kimyası; General Chemical Engineering; Physical Sciences; Polymers and Plastics; Organic Chemistry; Materials Chemistry; 3D printing; alginate; gelatin; PVA; scaffold; skin tissue